Content management systems in educational environment - Mateljan, Vladimir; Đambić Goran; Juričić, Vedran (2008)
This paper points out and describes the characteristics that are shared between the most of today's content management systems. The intention was to find what makes the core of today's content management systems, i.e. what defines them. To provide this, authors analyzed great number of systems on great number of attributes and features. Systems where compared and analyzed based on their approximate cost, supported operating systems and popularity. The result of those analyses indicates that the most represented and most appreciated characteristics are support, interoperability with other systems and existence of additional applications that can be integrated into web site, like blogs, newsletters and guest books.
Projekt MZOS
Projekt MZOS
ENG